The relationship between the geriatric nutrition risk index (gnri) and the prognosis of covid-19 in diabetic geriatric patients - Sivritepe, Rıdvan; Uçak Basat, Sema; Tiril, Serhat Mert (My University, 2023)
Background: Malnutrition is one of the important conditions that determine the course of patients in acute critical illnesses. This study evaluated the relationship between Geriatric Nutrition Risk Index (GNRI) and COVID-19 prognosis in geriatric diabetic patients. Patients and methods: In this study, 110 patients between the ages of 65 and 80 who were interned due to COVID-19 disease with a diagnosis of diabetes mellitus were included. Biochemical blood tests were analysed. The GNRI was calculated to assess the nutritional risk status. As a result of GNRI, the patients were divided into 4 groups according to their scores: severe risk (< 82 points), intermediate risk (82- -91 points), low risk (92-97 points) and no risk (>= >= 98 points). The length of stay, saturation levels, intubation status and discharge type of the patients were recorded. All parameters were compared in these groups. Results: According to the GNRI, 11.8% of the patients had severe malnutrition, 20.9% had moderate and 8.1% had mild malnutrition, while 59.0% had no risk of malnutrition. When patients are divided into four groups according to GNRI groups, age, urea, creatinine, lymphocyte, procalcitonin, leukocyte, thrombocyte, haemoglobin, spo2 and po2 levels, intubation, and intensive care referral rates were significantly different (p < 0.05). In the correlation analysis, a negative significant correlation was found between GNRI and height, length of hospital stays, d-dimer, CRP, leukocyte, neutrophil-lymphocyte ratio and neutrophil. Conclusions: There is a significant relationship between GNRI and the prognosis of COVID-19 in geriatric diabetic patients. Patients with a low GNRI score have a longer hospital stay, a higher need for intensive care and mechanical ventilation, and a poor prognosis.
Keywords: Geriatric Nutrition Risk Index (GNRI); COVID-19; Geriatrics; Malnutrition